Community Legal Assistance: Legal Socialization and Free Legal Clinics for the Restoration of Women Violence Victims’ Rights in Coastal Areas - Flora, Henny Saida; Maruf, Irma Rachmawati; Aiman, Muhammad; Karina, Ica; Herwantono, Herwantono (International Journal of Community Service (IJCS), 2025)
This study investigates the role of community legal assistance, focusing on free legal clinics and legal socialization initiatives, in supporting the recovery and restoration of rights for women victims of violence in Indonesia’s coastal regions. Employing a qualitative research methodology, the research analyzes field data, organizational reports, statutory frameworks, and direct interviews with stakeholders involved in legal advocacy. Results reveal that socio-legal interventions—especially targeted legal empowerment actions integrating psychosocial support with accessible legal services—have significantly improved women’s legal knowledge and helped many to secure protection orders, initiate police reports, and access community-based support networks. Nonetheless, cultural barriers, limited funding, and geographical constraints remain major challenges. The findings support policy recommendations for sustainable legal outreach in marginalized communities and underscore the importance of multi-sectoral partnerships to ensure effective rights restoration in coastal zones of Indonesia.